A novel heterogeneous multi-wire indirect arc directed energy deposition for in-situ synthesis Al-Zn-Mg-Cu alloy - Wang, Liwei (2023)
Funding Information: This work was supported by National Natural Science Foundation of China (Grant No. 51875168/52002112 ), Natural Science Foundation of Hebei Province (Grant No. E2019208089 ) and “Three-Three-Three Talent Project” Foundation of Hebei Province ( C20221022 ). Sichuan Province Science Funding for Distinguished Young Scholars ( 3NSFJQ0064 ). JPO acknowledges funding by national funds from FCT – Fundação para a Ciência e a Tecnologia, I.P., in the scope of the projects LA/P/0037/2020. Science and Technology Research Project of Colleges and Universities in Hebei Province (Grant No. BJK2022020 ). Publisher Copyright: © 2023 The Authors